Current methods of studying of the proliferative activity in experiment - T. V. Ivanenko; T. V. Abramova; N. V. Kuzo; S. V. Tyshchenko (Zaporozhye State Medical University, 2014)
Aims. To analyze the contemporary scientifi c literature data about methods of determining of the proliferative activity, as well as the choice of an optimal method for its assessing in tissues with expected low proliferative activity. Methods and results. This is necessary to select an optimal method for assessing of the proliferative activity in tissues with expected low proliferative activity. The article gives a detailed analysis of the current literature, describes various methods of studying of the proliferative activity of tissues in experiment. Conclusion. Bromodeoxyuridine is a versatile and highly effective marker of DNA replication and cell proliferation, allowing carrying out a dynamic observation of the experiment, including tissues with expected low proliferative activity. It can be widely used in chronic experiments on small rodents, in the simulation of various pathologies and studying the effect of pharmaceuticals on the activity of proliferation.